ETNOMATEMATIKA PADA ALAT MUSIK GAMELAN JAWA - Supriyono, Supriyono; Saputra, Agil Faisal; Purwaningsih, Wharyanti Ika (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This study aims to determine the mathematical concepts applied to Javanese gamelan musical instruments. The type of research used in this research is qualitative research with an ethnographic approach, namely describing Javanese gamelan musical instruments as a medium for learning Mathematics. Data obtained through interviews, observation, and documentation. The instrument in this study consisted of the main instrument, namely the researcher himself and auxiliary instruments in the form of interview guidelines, observation sheets, and documentation tools. The data validity technique used is method triangulation and source triangulation. The results of this study indicate that there are mathematical concepts that are applied to Javanese gamelan musical instruments such as one-dimensional geometry, namely the concept of lines, parallel lines and right angles, two-dimensional geometry, namely square, rectangle, circle, trapezoid, and triangle. three in the form of a tube, a sphere, and a truncated cone. With the existence of mathematical concepts in Javanese gamelan musical instruments, it is very possible for mathematics learning media to be designed using Javanese gamelan ethnomathematics so that mathematics contributes to the preservation of the nation's culture.